Investigating phase separation and mineralisation mechanics of mantis shrimp-derived fusion proteins - Koh, Jing Han (Nanyang Technological University, 2023)
Nature has long been a source of inspiration for the design of advanced biomaterials with exceptional properties. One such inspiration is the Club Mineralization Protein-1, that plays a crucial role in the biomineralization of the mantis shrimps’ dactyl clubs. CMP-113, a truncated fusion protein inspired by the CMP-1, was designed to incorporate liquid-liquid phase separation (LLPS)-promoting motifs to investigate how phase separation can potentially contribute to biomineralization. In the presence of various Hofmeister salts, coacervation of CMP-113 was assessed through brightfield microscopy, turbidity assays, dynamic light scattering (DLS) measurements and nuclear magnetic resonance (NMR) spectroscopy. Its resistance to 1,6-hexanediol treatment and re-entrant LLPS in presence of calcium chloride suggests that LLPS is not purely hydrophobic-driven but may potentially electrostatic interactions as well. Morphological observations of crystals formed in biomineralization experiments not only demonstrated CMP-113’s capability to form hydroxyapatite from solution, but its coacervation may also be imperative for accelerating crystal nucleation and growth. These findings were consistent with the wider literature on non-classical nucleation pathways of biomineralization. Future research on CMP-113 and its applications in biomaterials and materials science is anticipated to unveil new insights and open up exciting opportunities in the field of biomaterials research.